Неукладеність господарських договорів - погляд зблизька - Подоляк, С.А. (Часопис Київського університету права, 2009)
В статье автор рассматривает юридическую конструкцию «незаключенный договор» и ее соотношение с конструкцией «недействительный договор». С точки зрения синергетики обосновывается, что незаключенность договора является видом абсолютной недействительности - ничтожности. In the article author considers the economic contract as social-legal system. The analyze of valuation standards of economic contract concerning its force is made. The confrontation of legal constructions of economic contract - invalidity, nullity, loss of a contract - is made with legal point of view.